Findings in susceptibility weighted imaging in pediatric patients with migraine with aura. (September 2020) - Kellner-Weldon, Frauke; Lehmann, Vera Franziska; Breiding, Philipe Sebastian; Grunder, Lorenz; Muri, Raphaela; Pastore-Wapp, Manuela; Bigi, Sandra; Wiest, Roland; El-Koussy, Marwan; Slavova, Nedelina
Abstract: Background: Migraine with aura (MwA) in pediatric patients is clinically frequent. Clinically complex symptoms need to be differentiated to exclude mimicking conditions. Purpose: We hypothesize that MwA in children induces abnormalities readily visible in perfusion time to peak (TTP) maps as well as non-enhanced susceptibility weighted magnetic resonance imaging (SWI). Materials and methods: Between 2010 and 2018, we retrospectively evaluated symptoms and imaging of consecutive pediatric patients <18 years with MwA. We visually scored abnormalities on SWI and TTP maps in 12 regions of interest on both hemispheres on three axial slices, as normal, slightly, distinctly or severely abnormal. Results: 99 patients (69.7% female), mean age 14.07 y (±2.8) were included. Focally increased deoxygenation (FID) in SWI was present in 61.6%. FID on SWI was dominant for the left hemisphere (60.7% vs. 31.1%, ( p < .001)), and in 8.2% symmetric. Side of aura symptoms and contralateral hemispheric imaging alterations in patients with FID correlated significantly ( p = .002.). 61 of 99 patients had perfusion MR and 59% of these patients showed focal increase of TTP. Age correlated significantly with FID in SWI (r = -.248, p = .013) and increase of TTP in perfusion (r = -.252, p = .05). Focal abnormalities correlated significantly between SWI and TTP maps. Brain regions most often abnormal were the temporal superior, occipital and fronto-parietal regions. Conclusions: This study provides confidence in recognizing FID, and linking FID in SWI to acute MwA in pediatric patients. FID phenomenon had a left hemispheric significant dominance, and can be found bilaterally. Graphical abstract: Acute migraine with aura in pediatric patients is not vitally critical, but symptoms resemble stroke and thus trigger imaging frequently. For 99 patients with a final clinical diagnosis of migraine with aura, in whom MR imaging ruled out diffusion restriction and showed patency of major arterial vessels to exclude stroke, we reviewed patterns of venous vessels on susceptibility weighted magnetic resonance imaging (SWI). We found that focally increased deoxygenation (FID) in SWI can be attributed to migraine with aura in up to 61.6% in the acute phase. Most often FID was found in temporal superior, occipital and fronto-parietal regions with left hemispheric dominance and even bilaterally. Image 1 Highlights: Susceptibility-weighted imaging (SWI) frequently shows focally altered veins in pediatric acute migraine with aura (MwA). Increased oxygen extraction fraction in veins correlates with their hypointense and prominent appearance on SWI. Distribution of abnormal veins correlated well with disturbed perfusion time-to-peak maps. Abnormal veins in acute MwA have a temporal-occipital predominance, can be bilateral, and are age related. There is significant association between reported side of symptoms and contralateral hemispheric imaging alteration. Focally altered veins have a left hemispheric predominance on SWI.